Long‐term corrosion behaviour of EN AW‐6060‐T6 in an aluminium/carbon‐fibre reinforced polymer self‐piercing rivet joint. Issue 12 (4th December 2014) - Mandel, M.; Krüger, L.; von Hehl, Axel; Weise, Jörg
<x xml:space="preserve">Abstract</x> In this study, the corrosion behaviour of a self‐piercing rivet joint which consists of a sheet of the aluminium alloy EN AW‐6060‐T6 and a carbon‐fibre reinforced polymer laminate was investigated by multiple corrosion cycles, according to the standard VDA 621‐415. Due to the electrochemically quite different corrosion behaviour of the used materials the aluminium alloy is attacked by pitting corrosion close to and below the overlap of the joint. To investigate the amount of the corrosion attack the aluminium alloy was analysed by white‐light interferometry at the most attacked region in the joint after each corrosion cycle. Based on the results of the topographical scans the pit volumes were calculated in an area of 2 × 5 mm2. The plot of the pit volume versus the corrosion cycle number revealed a sigmoidal correlation that was adequately described by the Boltzmann function. Furthermore, due to the s‐shaped pit volume – cycle number correlation three stages of pitting corrosion were identified.